Analisis Kinerja Protokol LoRaWAN untuk Transmisi Data pada Skenario Urban Area - Fathan Muhammad; Adhitya Bhawiyuga; Dany Primanita Kartikasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Long Range Wide Area Network (LoRaWAN) is a type of network for wireless telecommunication area designed to enable remote communication with long distance communication and low bit rate. LoRaWAN can be used on communication networks that have a wide range using end devices. LoRaWAN offers a wide range of advantages to the challenge of IoT implementation, but the current implementation of LoRaWAN technology is still very limited, requiring feasibility testing and analysis to what extent LoRaWAN technology is capable of being implemented in urban areas in Indonesia. In this research, an analysis of the performance of the LoRaWAN protocol for data transmission with urban area scenarios in Malang City is carried out. The method used in this study is to simulates LoRaWAN protocol in Network Simulator 3 (NS-3) application by changing the parameters to determine the effect on the the number of end devices, radius of the gateway range, and data sending period to the parameters throughput and packet loss. From the results of research proved that for the use of protocol LoRaWAN in urban areas, the more end devices used, the greater the throughput value and the greater the value of packet loss obtained. In addition, the wider the area needed, the throughput and packet loss obtained are constant. And then, the larger the period of data transmission, the smaller the throughput value is obtained and the smaller the value of packet loss obtained.